PHYLLANTHUS NIRURI L TERHADAP IMUNITAS SELULER TIKUS - Ima Arum L; Purwanto AP; Henna Rya (Indonesian Association of Clinical Pathologist and Medical laboratory, 2011)
Typhoid fever is a problem in the developing country. Phyllanthus niruri L (meniran) is a traditional plant that can be used as an immunomodulator on cellular or humeral immunity. By giving Phyllanthus niruri L extract to patient who suffers typhoid fever can increase cellular immunity responses in intracellular bacteria infection (S.typhimurium).This research was an experimental study using the post test-only control group design to proof of the effects of Phyllanthus niruri L on cellular immunity balb/c infected by salmonella typhimurium. The samples were taken from thirty male Balb/c mice which were divided into five groups including P1 (infected by S.typhimurium and PnL extract 125 g), P2 (infected by S.typhimurium and PnL extract 250 g), P3 (infected by S.typhimurium and PnL extract 500 g), K1 (infected by S.typhimurium) and K2 (healthy mice). In this study was applied parametric test of one way ANOVA and post hoc test Bonfferoni. It was known that phyllanthus niruri L increased the number of activated lymphocytes and phagocyte ability of macrophage (p=0.003 and p=0.001, respectively). By Bonfferoni post hoc test resulted that no significantly difference between the treated groups (increased of dose). There were no significant difference between the number of leukocyte, the difference count of lymphocyte and the nitrite oxide produced among the treatment groups and controls. Phyllanthus niruri L dose 250 μg increased the activated lymphocyte and index phagocytes. To find out the effects of Phyllanthus niruri L compare to antibiotic and Phyllanthus niruri L combination, continuing/advancing studies are needed